2000
DOI: 10.1046/j.1439-0396.2000.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal environment on the digestion of broilers

Abstract: Summary Two experiments were conducted to determine the effect of thermal environment on the digestion of broilers. In both experiments the birds were exposed to three temperatures: 5, 21, and 32° C, and relative humidity was maintained at 60%. In experiment one, the amount of chyme in the whole digestive tract was decreased by the cold environment (5° C, 60% relative humidity) and increased by hot environment (32° C, 60% relative humidity), compared with control environment (20° C, 60% relative humidity). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 13 publications
0
48
0
1
Order By: Relevance
“…Também não está de acordo com a redução das atividades das enzimas proteolíticas (tripsina e quimotripsina) no intestino delgado de aves expostas ao calor verificada por Hai et al (2000).…”
Section: Resultsunclassified
“…Também não está de acordo com a redução das atividades das enzimas proteolíticas (tripsina e quimotripsina) no intestino delgado de aves expostas ao calor verificada por Hai et al (2000).…”
Section: Resultsunclassified
“…The broilers exposed to an environmental temperature of 32°C were subjected to heat stress, which resulted in decreased feed intake by 14%, as compared to those kept at thermo neutral zone temperature; this reduction in feed intake is to reduce metabolic heat production (Sahin et al, 2009). Hai et al (2000) reported that the activities of digestive enzymes trypsin, chymotrypsin and amylase were significantly reduced when animals were kept at high temperature (32°C) conditions. Heat stress also decreases the serum and liver concentrations of vitamins (C, E and A) and minerals (Fe, Zn, Se and Cr) and also influence the immune response of poultry (Donker et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…They lack sweat glands as in ruminant animals. There is consequential reduction in voluntary feed intake, so as to limit metabolic heat production (Hai et al, 2000) in order to lower the metabolic heat production. Moreover, they divert energy and other nutrients intended for growth, immunity and reproduction to thermoregulation, thereby limiting their productivity (Brake, 1987).…”
Section: Introductionmentioning
confidence: 99%